May ratio of neutrophil to lymphocyte be useful in predicting the risk of developing preeclampsia? A pilot study. (January 2015) - Kurtoglu, Emel; Kokcu, Arif; Celik, Handan; Tosun, Migraci; Malatyalioglu, Erdal
Abstract Objective: The aim of the study was to evaluate the relationship between neutrophil to lymphocyte ratio (NLR) and preeclampsia. Methods: Demographic data and laboratory tests for NLR of 203 pregnant women (73 normotensive pregnants, 23 pregnants with mild preeclampsia and 107 pregnants with severe preeclampsia) were retrospectively analyzed. Neutrophil to lymphocyte ratios were compared between the study groups. Results: Preeclamptic pregnant women had smaller gestation weeks, lower hemoglobin level and fetal birth weight than that of normal pregnant women. NLR in preeclamptic group was significantly higher than that of normal group (p = 0.023) and area under ROC curve was found statistically significant (p = 0.023). However, there was no statistically significant relationship between NLR and severity, proteinuria level, subjective symptoms and onset time of the disease. Conclusion: The findings showed that the measurement of NLR periodically may be useful to predict high-risk pregnancies in terms of preeclampsia, but further studies are needed to determine its contribution.